Peranan Badan Perencanaan Pembangunan Daerah Dalam Perncanaan Pembangunan Daerah Di Kabupaten Halmahera Timur - Rorano, Alva Martoms; Pangkey, Masye S (JURNAL ILMU ADMINISTRASI (JIA), 2013)
Abstract: This study aims to determine the role of the Regional Development Planning Agency in Regional Development Planning Process in East Halmahera. In this research, using qualitative research methods and techniques of qualitative data analysis. data collection techniques in this study include: (1) Interview, (2) documentation, and (3) Observation. The stages-resistant performed in analyzing the data, are: (1) Data Editing, (2) Data Reduction, and (3) Data Interpretation. Based on the results of research conducted, showing that: (1) In the process of regional planning, Regional Planning Board of East Halmahera certainly plays an important role in accommodating all available resources to formulate local development planning, (2) Role of Regional Development Planning Board East Halmahera can walk though the process is still there are issues that affect the development planning of factors both internal and external factors. Internal factors of the Halmahera Bappeda itself, among others, the ability of human resources is not adequate, facilities and infrastructure, and coordination are not yet optimal. While external factors which other officials unprepared planning data, other officials have not been the focus in the planning, implementation activities are not always on time according to the fiscal year due to some areas difficult to reach (geographic factors), and the involvement of stakeholders in the planning process is low. Keywords: Role, Bappeda, development planning process